Probing the changes of carotenoids in Microcystis flosaquae under environmental perturbations by two‐dimensional Raman correlation spectroscopy. (12th November 2019) - He, Shixuan; Xie, Wanyi; Fang, Shaoxi; Zhang, Ping; Li, Zhe; Zhou, Daming; Zhang, Yongna; Zhang, Zhiyou; Guo, Jinsong; Du, Jinglei; Du, Chunlei; Wang, Deqiang
Abstract: Raman mapping spectra of Microcystis flosaquae ( M. flosaquae ) subjected to environmental perturbations were used to study the correlations among the characteristics of M. flosaquae by two‐dimensional (2‐D) Raman correlation spectroscopy. Overlapping Raman characteristics of the carotenoids in M. flosaquae and their differences in algal growths were shown in the 2‐D synchronous and asynchronous correlation spectra. The asynchronous correlation Raman spectra demonstrated the accumulation of carotenoids in M. flosaquae under normal culture condition and environmental perturbations. High light flux obviously led to the accumulation of β‐carotene in M. flosaquae in comparison with normal culture condition. The results showed that 2‐D Raman correlation spectroscopy can be used to analyze the correlation of complex changes of the Raman characteristics of M. flosaquae induced by different environmental conditions to assess the accumulation of the carotenoids in algae and to predict the algal growth phases. Abstract : Overlapping Raman characteristics of the carotenoids in M. flosaquae and their differences in algal growth were shown in the two‐dimensional (2‐D) synchronous and asynchronous correlation spectra. The asynchronous correlation Raman spectra demonstrated the accumulation of the carotenoids in M. flosaquae under environmental perturbations. 2‐D Raman correlation spectroscopy can be used to assess the accumulation of the carotenoids in algae and to predict algal growth phases.